ANALYSIS OF FINANCIAL PERFORMANCE OF PT ASTRA AGRO LESTARI TBK IN THE PERIOD BEFORE AND DURING THE COVID-19 PANDEMIC USING THE ECONOMIC VALUE ADDED APPROACH - Hanifah Nur Hidayah; Baniady Gennody Pronosokodewo; Sri Suryaningsum (Count : Journal of Accounting, Business and Management, 2023)
The COVID-19 pandemic has made various changes in every aspect of life, one of which is the industrial world. Economic uncertainty raises a lot of speculation which sectors will benefit and lose. This study uses the Economic Value Added (EVA) approach. This method is an indicator of the added value of an investment every year in a company, with this method can see the added economic value during a certain period and can be one way to assess the company's performance. This study aims to provide an overview of the impact on PT Astra Agro Lestari Tbk during the Covid-19 pandemic, and analyze the company's financial performance using the Economic Value Added (EVA) analysis method. This study uses a descriptive analysis technique with a quantitative approach. This study uses secondary data in the form of financial statements obtained from the financial statements of PT Astra Agro Lestari Tbk for the 2018-2021 period.